2021
DOI: 10.1021/acsami.1c15503
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Mediated Kinetic Control of Fe3+–Tannic Acid Complexation for Interface Engineering

Abstract: Supramolecular self-assembly of Fe 3+ and tannic acid (TA) has received great attention in the fields of materials science and interface engineering because of its exceptional surface coating properties. Although advances in coating strategies often suggest that kinetics in the generation of interface-active Fe 3+ -TA species is deeply involved in the film formation, there is no acceptable elucidation for the coating process. In this work, we developed the enzyme-mediated kinetic control of Fe 2+ oxidation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…It is therefore required to explore the novel reactions by using the enzyme outside of the protease family. Enzymatic oxidation is a typical candidate for eliciting the self‐assembly, considering some reports demonstrated that the self‐assembly is induced via enzymatic oxidation [22a,b] . Being integrated with the self‐assembly, enzymatic oxidation would facilitate the development of the assemblies with prominent physicochemical properties [83]…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore required to explore the novel reactions by using the enzyme outside of the protease family. Enzymatic oxidation is a typical candidate for eliciting the self‐assembly, considering some reports demonstrated that the self‐assembly is induced via enzymatic oxidation [22a,b] . Being integrated with the self‐assembly, enzymatic oxidation would facilitate the development of the assemblies with prominent physicochemical properties [83]…”
Section: Discussionmentioning
confidence: 99%
“…SCNE has recently advanced to catalytic SCNE, [51,[67][68][69][70] in which cells are empowered in function by external enzymes and chemical catalysts present in or on the shell, and the biochemical pathways of the cells could be rewired or reprogramed by coupling between innate and external reactions. [1] ESMHs or CMs per se could act as a catalyst due to diverse functional groups.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the kinetics of MPN film formation could be readily tuned by the glucose oxidase-catalyzed reaction of d -glucose, which produces hydrogen peroxide to accelerate the oxidation of Fe 2+ to Fe 3+ in MPN films composed of Fe III –TA complexes. 352 The optimized kinetics of generating Fe 3+ –TA species facilitated film formation, producing MPN films with 9 times higher thickness compared to the air oxidation-based method. In another example, tyrosinase was used to expand the toolbox for MPN assembly by converting monophenol groups of molecules to catechol groups.…”
Section: Engineered Nanostructured Particles From Natural Building Bl...mentioning
confidence: 99%